Judicial remedies for illegal impeachment under the Nigerian constitution: a critique of the case of Ladoja vs. Independent National Electoral Commission & Ors - Sani, Abdullahi; Md Ismail, Che Thalbi; A. Rahman, Aspalella (2016)
The Nigerian constitution makes provision for the impeachment of public officers- the President, Vice President, Governor and Deputy Governor. Any such impeachment conducted not in accordance with the constitutional provision is declared illegal by the courts and the public officer concerned reinstated as a remedy.In the case under review, a state Governor was illegally impeached but reinstated after eleven months as a result of which he sought for a remedy to enable him complete the four-year tenure as provided by the constitution which was refused by the court. The paper having examined the decision found that it is not predicated on a sound legal pedestal as it is fraught with wrong interpretation of the relevant constitutional provision and injustice. Consequently, the remedy granted to the Governor is grossly inadequate in the circumstance. We recommend that the courts should be active in interpreting the tenure of illegally impeached public officers as not to include the time they spent out of office. This is in line with the letters and spirit of the constitution and to advance adequate remedy in the circumstance.